Application of the whole-course care model (IWF/C Care) for postintensive care syndrome based on an early warning system in critically ill patients: a randomised controlled trial study protocol - Xia Zhang; Xiaohui Liu; Jianmei Long; Yonghu Chang; Huiming Gao; Junxi Chen; Rujun Hu (BMJ Open, 2023)
Introduction Critically ill patients are at risk of developing postintensive care syndrome (PICS), which is manifested by physical, psychological and cognitive impairment. Currently, there are no programmes that combine early warning systems with interventions for PICS. We hypothesise that a comprehensive care model for PICS based on an early warning system would reduce medical costs and the incidence of PICS.Methods and analysis The Intensive Care Unit (ICU) -Ward-Family/Community whole-course care (IWF/C Care) trial will be a unicentric, randomised, controlled trial. A total of 138 ICU patients from two ICUs at a university hospital in Guizhou province, China, will be enrolled in February 2023. The inclusion criteria are an age of 18 years or older, an ICU stay of more than 48 hours, provide informed consent and the ability to communicate normally. Patients will be followed for 12 months and randomised in a 1:1:1 ratio to three groups.Interventions Patients in intervention group 1 will be assessed by the PICS early warning system within 24 hours of ICU discharge, and precise interventions will be carried out according to the results; that is, high-risk patients will receive care based on the IWF/C Care model and low-risk patients will receive routine care. All patients in intervention group 2 will receive care based on the IWF/C Care model. The control group will receive routine care. The primary endpoints are the incidence of PICS and quality of life. The secondary endpoints include the incidence of adverse events: the unplanned readmission rate, cost-effectiveness, and the experiences and feelings of patients receiving care based on the IWF/C Care model. The incidence of PICS will be measured at ICU discharge, general ward discharge, the home/community stage and 1 month and 3, 6, 9, and 12 months after discharge.Ethics and dissemination Ethics approval was obtained from Biomedical Research Ethics Committee of the Affiliated Hospital of Zunyi Medical University (approval number: KLL-2022-780). The results of this study will be distributed through peer-reviewed journals.Trial registration number ChiCTR2300068135.